Importance Performance Analysis (IPA) Method To Measure Satisfaction of Procurement of Goods and Services PT Perkebunan Nusantara VIII (Persero) Partner - Abdul Malik Sayuti; Wiharsono, Habsari Anon (Jurnal Riset Bisnis dan Investasi, 2022)
Meeting the needs of core business, PT Perkebunan Nusantara VIII has been procuring goods and services since the company was founded with bidding system. In its implementation there are obstacles that are felt by partners. Along with the development, problem solving and adjustment to the COVID-19 pandemic conditions, Holding Perkebunan Nusantara created the Integrated Procurement System (IPS) as a forum for e-procurement activities.Based on it, there are several complaints submitted by partners that affect their satisfaction. With the aim of measuring partner satisfaction and determining satisfaction indicators that need to be improve, the Importance Performance Analysis method is used to map which cooperation indicators are partners' priorities and which indicators still have low performance. The results of the study found that partners were satisfied with the cooperation that occurred, but there are some indicators that still have low performance compared to partners' expectations, namely communication with partners and problem solving.